Impact of the COVID-19 pandemic on ST – elevation myocardial infarction management in a reference center of northern Peru - Carrión Arcela, Jean Pierre (2021)
Objective. To evaluate the impact of the COVID-19 pandemic on the ST–Elevation myocardial infarction (STEMI) management in a reference center of northern Peru. Methods. Observational, analytical, retrospective cohort-type study, derivated from the Acute Coronary Syndrome registry of the Almanzor Aguinaga Asenjo National Hospital. The characteristics of the patients with STEMI and their 30-day outcomes were compared in 02 cohorts according to the time of medical care: prior to the pandemic or during the pandemic. Results. During the COVID-19 pandemic, hospitalizations for STEMI decreased by 53%, there was a greater use of fibrinolysis to the detriment of primary angioplasty, with increases in the time of first medical contact (100 vs. 240 minutes, p = 0.006) and ischemic time to percutaneous coronary intervention (900 vs. 2880 minutes, p <0.001). This generated a higher frequency of post-infarction heart failure (21.1% vs. 46.7%, p = 0.002) and a lower left ventricular ejection fraction at discharge (49.2 +/- 8.6 vs 44.8 +/- 9.3, p = 0.009), without an increase in in-hospital cardiovascular mortality. Conclusions. The COVID-19 has had a negative impact on the treatment of patients with STEMI. We found less hospitalizations, prolonged reperfusion times, and higher frequency of post-infarction heart failure and lower left ventricular ejection fraction at discharge.